Microbial Ecology of Qatar, the Arabian Gulf: Possible Roles of Microorganisms - Al-Thani, Roda F.; Yasseen, Bassam T. (Frontiers in Marine Science, 2021)
The Arabian Gulf ranks among the world’s most arid and warm regions; the land has high salinity levels with many Sabkhas and receives little precipitation. This region holds about one-third of the world’s oil supply. Qatar is the leading gas producer worldwide, which raises many concerns about the pollution of the sea, groundwater, and soil. Thus, the Arabian Gulf area has paid particular attention to environmental studies since the environmental status of this region imposed unique biological diversity, and microbial ecology has gained special importance following the identification of promising roles of microorganisms. This review article discusses the microbial ecology at the main habitats of the State of Qatar. We discuss important principles for successful ecological restoration and future perspectives of using biological approaches to solve many problems related to health, the economy, and agriculture. There are at least five microbial communities that have been recognized at the Qatari habitats: marine environment, salt marshes and mangrove forests, the arid lands (including dune communities), wetlands (including pond communities), and Rawdahs (including the Ghaf tree communities). Although, the environmental conditions of this region are almost the same, these habitats are compared with those at other countries of the Arabian Gulf whenever necessary, as each habitat has its own peculiar characteristics. Some case studies are presented to describe the biochemical characterizations of bacterial isolates from soils and leaf surface of native plants, including halophytes and xerophytes at these habitats. These studies rarely went beyond the general identification at species levels. There is a discussion about the possible roles of microorganisms at the rhizosphere, non-rhizosphere, and phyllosphere, and using plant exudates to control microbial activity. However, modern approach (culture-independent methods) addressing these topics has opened the door for deeper investigations, and to explore the roles played by microorganisms at these habitats. These methods have already begun during the last decade as serious step to solve many environmental issues. In the future, it is very likely that microorganisms will be used to tackle many pollution issues, as well as health, agricultural, and economic problems.